Legal Implications of The Use of Permit to Open State Land as Collateral for Debt: A Case Study of Regional Regulation of Balikpapan City No. 1 of 2024 - Sari, Fitrizka Eka; Koeswahyono, Imam; Masykur, Hamidi (IJBLE Scientific Publications Community Inc., 2023)
Indonesia is a country abundant in natural resources and human resources, aiming to provide prosperity for its people. The need for credit and the provision of credit facilities require collateral. The government has established a credit guarantee institution capable of providing legal certainty and legal protection. One of these institutions is the Mortgage Rights institution regulated by Law Number 4 of 1996 concerning Mortgage Rights on Land and Related Objects (UUHT). In the city of Balikpapan, East Kalimantan, there is a legal product in the field of land management based on regional autonomy, adhering to the principle of decentralization that grants authority through the enactment of Regional Regulation Number 1 of 2014 concerning State Land Opening Permits, known as